COUNSELING ABOUT REGARDING THE FLOW OF EMERGENCY INSTALLATION SERVICES/EMERGENCY UNITS IN THE HOSPITAL AT THE AR-RAUDHAH MOSQUE, KARYA BAKTI STREET, BAMBU KUNING WARD, TENAYAN RAYA DISTRICT, PEKANBARU CITY. - Tonis, Marian; Firdaus, Muhammad; Suryandartiwi, Wiwik; Yuliana, Anastasya Shinta (Awal Bros Journal of Community Development, 2023)
The Emergency Department is one of the units in a hospital that provides initial treatment of patients, according to the level of emergency. The difference between ER and ER. ER stands for emergency department, while ER stands for emergency installation. Both the ER and the ER have the same handling principles. Both provide appropriate and prompt treatment for emergency or life-threatening medical conditions. A screening officer will sort patients into triage groups. The triage group consists of red triage, yellow triage, green triage, and black triage. The action of ER / ER services starts from the patient coming until the patient is finished. Therefore, to inform the local community about the flow of emergency room services, we conduct counseling. After all these stages were carried out, a planning of counseling activities for the flow of emergency room services was obtained at the Ar-Raudhah mosque.